The Global Spanish Empire Five Hundred Years of Place Making and Pluralism - Beaule, Christine D.; Douglass, John G. (2020)
The Spanish Empire was a complex web of places and peoples. Through an expansive range of essays that look at Africa, the Americas, Asia, the Caribbean, and the Pacific, this volume brings a broad range of regions into conversation. The contributors focus on nuanced, comparative exploration of the processes and practices of creating, maintaining, and transforming cultural place making within pluralistic Spanish colonial communities. The Global Spanish Empire argues that patterned variability is necessary in reconstructing Indigenous cultural persistence in colonial settings. The volume's eleven case studies include regions often neglected in the archaeology of Spanish colonialism. The time span under investigation is extensive as well, transcending the entirety of the Spanish Empire, from early impacts in West Africa to Texas during the 1800s. The contributors examine the making of a social place within a social or physical landscape. They discuss the appearance of hybrid material culture, the incorporation of foreign goods into local material traditions, the continuation of local traditions, and archaeological evidence of opportunistic social climbing. In some cases, these changes in material culture are ways to maintain aspects of traditional culture rather than signifiers of new cultural practices. The Global Spanish Empire tackles broad questions about Indigenous cultural persistence, pluralism, and place making using a global comparative perspective grounded in the shared experience of Spanish colonialism.